2021
DOI: 10.3389/fdmed.2021.651219
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Reparative Processes in the Inflamed Dental Pulp

Abstract: Research over several decades has increased our understanding of the nature of reparative and regenerative processes in the dental pulp, at both the cellular and molecular level. However, advances in scientific knowledge have not translated into novel clinical treatment strategies for caries-induced pulpitis. This narrative review explores the evidence regarding the ability of inflamed pulp tissue to heal and how this knowledge may be used therapeutically. A literature search and evidence analysis covering bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 100 publications
0
8
0
Order By: Relevance
“…The general wound-healing process is a highly programmed process that is involved in various cellular and molecular events. It includes hemostasis, inflammation, proliferation, and remodeling phases ( El karim et al 2021 ). In the present study, PCNA expression in moderate carious teeth indicated that the inflammatory and proliferative phases have overlapped during caries progression, and when DPC was performed, acute inflammation might have been triggered again due to pulp exposure ( Guo and DiPietro 2010 ; El karim et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The general wound-healing process is a highly programmed process that is involved in various cellular and molecular events. It includes hemostasis, inflammation, proliferation, and remodeling phases ( El karim et al 2021 ). In the present study, PCNA expression in moderate carious teeth indicated that the inflammatory and proliferative phases have overlapped during caries progression, and when DPC was performed, acute inflammation might have been triggered again due to pulp exposure ( Guo and DiPietro 2010 ; El karim et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It includes hemostasis, inflammation, proliferation, and remodeling phases ( El karim et al 2021 ). In the present study, PCNA expression in moderate carious teeth indicated that the inflammatory and proliferative phases have overlapped during caries progression, and when DPC was performed, acute inflammation might have been triggered again due to pulp exposure ( Guo and DiPietro 2010 ; El karim et al 2021 ). As a result, the wound-healing process in carious teeth underwent a more complex process that is mainly affected by the surrounding environment (e.g., infection, immune regulation).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that acute inflammation is an important protective immune response during infections and is essential for healing of cariously inflamed pulp (Cooper et al, 2014 ; El Karim et al, 2021 ). However, chronic and excessive inflammation is a driver of host tissue injury seen in many severe infectious diseases, and it must therefore be carefully regulated for an optimal healing response.…”
Section: Discussionmentioning
confidence: 99%
“…In teeth with deep caries and exposed pulp, bacteria directly invade the dental pulp leading to irreversible pulpitis. The microflora in such lesions is mixed but dominated with Gram‐positive bacteria (Hahn et al, 1991 ; Love & Jenkinson, 2002 ; Zheng et al, 2019 ) that lead to the development of inflammatory and immune events in the dental pulp, the molecular and cellular determinants of which remain largely unknown (El Karim et al, 2021 ; Jontell et al, 1998 ). The NLRP3 inflammasome is expressed in the dental pulp (Song et al, 2012 ) and plays an important role in sterile pulp inflammation (Al Natour, Lundy, et al, 2021 ), but, its role in caries‐induced pulp inflammation is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…These treatments include a spectrum of modalities including indirect pulp capping, direct pulp capping and pulpotomy (partial or complete). Although not novel, VPT has recently emerged as a promising biologically based treatment due, in part, to advances made in the scientific field, including the introduction of bioactive hydraulic calcium silicate cements (Nair et al, 2008; Parirokh et al, 2018) as well as advances in pulp biology that have improved clinicians' understanding of the biological and reparative processes occurring in the injured dental pulp (Duncan, Cooper, & Smith, 2019; El Karim, Cooper, et al, 2021). Consequently, a plethora of clinical studies reporting on the outcome of VPT have been published over the last two decades and have demonstrated high success rates (Asgary et al, 2017; Bjørndal et al, 2017; Taha & Abdulkhader, 2018).…”
Section: Introductionmentioning
confidence: 99%